2007
DOI: 10.1097/01.ogx.0000265998.40912.5e
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal Pyrexia: A Review. Part I

Abstract: Obstetricians & Gynecologists, Family Physicians Learning Objectives: After completion of this article, the reader should be able to recall that world wide puerperal sepsis is a leading cause of maternal mortality, state that many of the predisposing factors are preventable, explain that both nosocomial infections as well as exogenous infections are serious factors, and relate that septic techniques and antibiotics can play a major role in reducing the incidence of puerperal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 33 publications
4
131
0
2
Order By: Relevance
“…However, puerperal infections are still reported as one of the major causes of maternal death, accounting for up to 15% of deaths (2)(3)(4). Puerperal sepsis is a polymicrobial infection of the genital tract caused by bacteria that normally inhabit the birth canal (5). In contrast, the term puerperal infection is used for genital tract infection along with other generalized infections that are incidental to pregnancy, such as tuberculosis, malaria, H1N1 influenza, and other endemic infections, including scrub typhus and dengue hemorrhagic fever (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, puerperal infections are still reported as one of the major causes of maternal death, accounting for up to 15% of deaths (2)(3)(4). Puerperal sepsis is a polymicrobial infection of the genital tract caused by bacteria that normally inhabit the birth canal (5). In contrast, the term puerperal infection is used for genital tract infection along with other generalized infections that are incidental to pregnancy, such as tuberculosis, malaria, H1N1 influenza, and other endemic infections, including scrub typhus and dengue hemorrhagic fever (5).…”
Section: Introductionmentioning
confidence: 99%
“…Then bacteria are able to reproduce and reach numbers in excess of 10 5 per milliliter of amniotic fluid 27 . Risk factors for the development of maternal sepsis include home birth in unhygienic conditions, low socioeconomic status, poor nutrition, primiparity, anaemia, prolonged rupture of membranes, prolonged labour, multiple vaginal examinations in labour (more than five), caesarean section, multiple pregnancy, artificial reproductive techniques, overweight and obstetrical manoeuvres 14,28 .…”
Section: Risk Factors and Routes Of Infection In Pregnancymentioning
confidence: 99%
“…Some of patient factors predisposing to the development of puerperal infection include home birth in unhygienic conditions, prolonged labor with or without rupture of membranes, multiple vaginal examinations in labor, obstetrical maneuvers, retained secundines within the uterus and postpartum hemorrhage (3). In addition, it has been shown that pre-existing medical problems, febrile illness or taking antibiotics during 2 weeks prior to presentation, operative vaginal delivery and cesarean section may be associated with sever puerperal infections (5).…”
Section: Introductionmentioning
confidence: 99%
“…Puerperal sepsis causes at least 75000 maternal deaths every year, mostly in low-income countries (4). Postpartum infections may also result in maternal morbidities which includes a wide range of maternal complications such as septicemia, endotoxic shock, peritonitis or abscess formation leading to surgery and compromised future fertility (3). For each maternal death associated with puerperal infections, around 50 women experience life-threatening morbidity from sepsis (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation